Brexit as Politic Discourse in Examining the Social Construction of Crisis - Vidi Regina Juliana Yusuf (Jayapangus Press, 2025)
Brexit, the United Kingdom’s decision to leave the European Union following the 2016 referendum, represents one of the most impactful political events in contemporary European history. This article aims to contribute theoretically by expanding the application of constructivism in the study of international relations, while also offering practical insights into how crisis discourse can be utilized to shape public opinion and direct national policy. Using Alexander Wendt’s constructivist approach and the method of Critical Discourse Analysis, this study demonstrates how political actors such as Boris Johnson and Nigel Farage reconstructed the meaning of the UK’s EU membership as a threat to national sovereignty. Through emotional rhetoric such as “take back control” and media support that amplified fears about immigration and foreign interference, the crisis was positioned as an existential struggle over identity and national independence. The analysis confirms that political reality is not solely determined by material structures but is shaped by socially constructed meanings through interaction, language, and identity.